2015
DOI: 10.1016/j.jet.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing social value of information

Abstract: This paper examines the social value of information in symmetric Bayesian games with quadratic payo↵ functions and normally distributed public and private signals. The main results identify necessary and su cient conditions for welfare to increase with public or private information. Using the conditions, we classify games into eight types by welfare e↵ects of information. In the first type, welfare necessarily increases with both public and private information.In the second type, welfare can decrease, but only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…That is, 7 A full discussion of this point is relegated to the supplementary Appendix B. 8 Such perverse effects (in a perfectly-private/perfectly-public two-signal world) were documented iby Ui and Yoshizawa [46]. In an application to the Cournot setting with β = c = 0, so that π = (M + 1)/2, Ui and Yoshizawa [46, Section 4.1] reported that for M = 2 more public information is good for profits (and for welfare).…”
Section: The Incentives For Information Acquisitionmentioning
confidence: 99%
“…That is, 7 A full discussion of this point is relegated to the supplementary Appendix B. 8 Such perverse effects (in a perfectly-private/perfectly-public two-signal world) were documented iby Ui and Yoshizawa [46]. In an application to the Cournot setting with β = c = 0, so that π = (M + 1)/2, Ui and Yoshizawa [46, Section 4.1] reported that for M = 2 more public information is good for profits (and for welfare).…”
Section: The Incentives For Information Acquisitionmentioning
confidence: 99%
“…Because of the best-response correspondence, if a potential function is strictly concave, then a Bayesian Nash equilibrium is a unique maximizer of the potential function (Ui, 2009). Basar and Ho (1974) was the first to use Radner's results to study LQG games that are not teams, followed by many studies on information sharing in oligopoly (Clark, 1983;Vives, 1984;Gal-Or, 1985) and social value of information (Morris and Shin, 2002;Angeletos and Pavan, 2007;Ui and Yoshizawa, 2015), among others. LQG games in these studies are Bayesian potential games.…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature on information economics, following Morris and Shin (2002), includes discussions on the interrelationships between strategic behavior and public information. Angeletos and Pavan (2007) and Ui and Yoshizawa (2013) provide characterizations of those interrelationship using general Bayesian games. 1 These studies consider simultaneous-move games with uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…2 Angeletos and Pavan (2007) and Ui and Yoshizawa (2013) consider Cournot games as an industrial organization application. In another branch of the literature, Vives (1984Vives ( , 1988Vives ( , 2008Vives ( , 2011 and Myatt and Wallace (2013) analyze large Cournot games.…”
Section: Introductionmentioning
confidence: 99%